Impact of values on the learning approaches of Chinese construction students in Hong Kong. Issue 5 (19th August 2014) - Leung, Mei-yung; Dongyu, Chen; Liu, Anita M.M.
Abstract : Purpose: This paper aims to explore the influence of personal values on students' learning behaviours. Hong Kong construction students are often criticized, by both practitioners and educators, as rote learners. To improve students' learning processes, extensive research on a variety of aspects of construction education has been conducted. However, limited attention has been paid to the influence of personal values on students' learning behaviours. The impact of personal value factors on the learning approaches of Chinese construction students in Hong Kong is investigated. Design/methodology/approach: A questionnaire survey was conducted to ethically-Chinese construction students in four universities in Hong Kong. A total of 820 questionnaires were distributed and 431 valid returns were collected. Findings: The survey identified six influential values (namely personal integrity, conservatism, determination, discipline, inter-personal relationships, and achievement), and shows that students who emphasize the virtues of personal integrity, determination, and a positive attitude toward achievement are better able to handle their interpersonal relationships, which will eventually lead them to engage in deep learning. Originality/value: Work to develop appropriate value systems is thus recommended in freshmen courses, as is the use of cooperative learning approaches. Such value systems will have a long-term influence on the learning approaches of construction students.